Pengaruh Aplikasi Pupuk Organik Enrichment LOB 2.0 terhadap Total Populasi Mikroba Pada Tanah Marjinal di PT. Great Giant Pineapple Lampung Tengah - Haholongan, Reynaldi Febriyan (UNIVERSITAS HAMZANWADI, 2025)
Soil fertility is a soil condition that can support plant growth properly. Soil fertility is strongly influenced by many factors, one of which is the microbial population in the soil. Microbial populations are important due to their important role in degrading complex nutrients into simpler nutrients to be utilized by plants and other soil biota. The application of fertilizers and plows is done to support microbial growth in marginal soils. The types of fertilizers used were P0 (compost + biochar 1.75%), P1 (compost with 10t/ha biochar application), P2 (compost + biochar 1.75% + vermicompost 1.5%), and P3 (compost + biochar 1.75% + vermicompost 1.5% added microbial enrichment). From this study, the results of Split Plot ANOVA showed that there was a significant effect on month 1 and 3 observations, both on fungi and bacteria. Treatments that had a significant effect were further tested with Tukey's HSD. The best treatment based on the comparison of the mean in the 1st month fungal observation is P3, while in the 3rd month fungus and bacteria is P0.